Using altered auditory feedback to study pitch compensation and adaptation in tonal language speakers - Tang, Ding-lan (Frontiers in Human Neuroscience, 2024)
Human speech production is strongly influenced by the auditory feedback it generates. Auditory feedback-what we hear when we speak-enables us to learn and maintain speaking skills and to rapidly correct errors in our speech. Over the last three decades, the real-time altered auditory feedback (AAF) paradigm has gained popularity as a tool to study auditory feedback control during speech production. This method involves changing a speaker's speech and feeding it back to them in near real time. More than 50% of the world's population speak tonal languages, in which the pitch or tone used to pronounce a word can change its meaning. This review article aims to offer an overview of the progression of AAF paradigm as a method to study pitch motor control among speakers of tonal languages. Eighteen studies were included in the current mini review and were compared based on their methodologies and results. Overall, findings from these studies provide evidence that tonal language speakers can compensate and adapt when receiving inconsistent and consistent pitch perturbations. Response magnitude and latency are influenced by a range of factors. Moreover, by combining AAF with brain stimulation and neuroimaging techniques, the neural basis of pitch motor control in tonal language speakers has been investigated. To sum up, AAF has been demonstrated to be an emerging tool for studying pitch motor control in speakers of tonal languages.